Teachers’ beliefs and strategies in facilitating children’s risky play: A systematic literature review - Amanda, Rahma Yulista; Waluyo, Edi; Formen, Ali; Ary, Deasylina Da; Pranoto , Yuli Kurniawati Sugiyo (Universitas Jambi, Indonesia, 2026)
Risky play poses a dilemma for early childhood educators, raising concerns about children’s safety and institutional accountability. Teachers’ tolerance toward risky play is often influenced by their beliefs, confidence, and pedagogical competence. This study examines teachers’ beliefs and strategies in facilitating risky play through a Systematic Literature Review (SLR) guided by PRISMA procedures. Eleven empirical studies published between 2021 and 2025 were selected from major academic databases. The findings indicate that teachers employ strategies such as creating supportive environments, providing responsive supervision, offering physical and verbal scaffolding, explaining potential risks, and encouraging children’s autonomous exploration. Teachers’ beliefs significantly shape the implementation and sustainability of risky play practices. Educators with strong confidence in the developmental value of controlled risk tend to adopt facilitative roles rather than restrictive ones, enabling children to assess risks, build resilience, collaborate with peers, and develop independence. The review highlights the importance of strengthening teachers’ professional competence and institutional support to optimize meaningful risky play experiences.